Seven economic facts about the U.S. racial wealth gap - Kristen Broady; Darlene Booth-Bell; Taylor Griffin (Federal Reserve Bank of Chicago, 2022)
Using data from the 2019 Survey of Consumer Finances and the U.S. Census Bureau, along with data and research from other sources, this paper presents seven economic facts about the racial wealth gap in the U.S. We present data on racial disparities in income, employment, homeownership, education, access to credit, and retirement savings - all factors that contribute to a significant and persistent gap in net worth between households of different races and ethnicities, particularly between Black households and White households. While none of the economic factors listed fully explains the racial wealth gap, each factor, along with a history of racism and discrimination has contributed to the extreme wealth inequality in America today.
Keywords: D31; D63; E24; I24; 330; Wealth Inequality; Income; Education; Credit